Transgene and islet cell delivery systems using nano-sized carriers for the treatment of diabetes mellitus. (1st January 2017) - Ito, Kiyonori; Ookawara, Susumu; Ishibashi, Kenichi; Morishita, Yoshiyuki
ABSTRACT: Gene therapy that targets the pancreas and intestines with delivery systems using nano-sized carriers such as viral and non-viral vectors could improve the control of blood glucose levels, resulting in an improved prognosis for patients with diabetes mellitus. Allogenic pancreatic islet cell transplantations using such delivery systems have been developed as therapeutic options for diabetes mellitus. This review focuses on transgenes and islet cell delivery systems using nano-sized carriers for the treatment of diabetes mellitus.